THE ROLE OF TEACHERS IN IMPROVING THE CONCENTRATION OF CHILDREN WITH ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD) AGED 5-6 YEARS - Adiningtyas, Laila Amelia; Wahyuni, Akhtim (Academic Journal Research, 2024)
Objective: This study aims to explore the role of early childhood education teachers in supporting children with ADHD, particularly in the B1 kindergarten class at RA Depag 1 Mojokerto, and to assess how teachers can enhance the learning environment for children with attention difficulties. Methods: A descriptive qualitative approach was employed, using data collected through direct observations, interviews with teachers and the principal, and documentation. The research was conducted over four months, from February to May 2024, at RA Depag 1 Mojokerto. Data analysis followed the interactive model by Miles and Huberman, including data reduction, display, and verification. Results: The study found that children with ADHD in the classroom face challenges in maintaining focus, which affects both academic performance and classroom behavior. Teachers provide individualized support by using personal approach strategies and creating a conducive classroom environment. These strategies include placing ADHD children near the teacher's desk, reducing distractions, and offering direct support. The involvement of parents and school counselors also plays a crucial role in improving concentration. Novelty: This research emphasizes the importance of a comprehensive approach that involves teachers, parents, and professionals in managing ADHD in early childhood education. The study highlights the significance of tailored interventions, classroom environment adjustments, and collaborative efforts to support children with ADHD, contributing to more effective educational practices for children with special needs.